The Development of MONOTIKA (Monopoly Mathematics) Learning Media in Algebraic Material for Junior High School Students in Grade VII - Shafira Ramadhani; Leonard Leonard; Muh. Aripin Nurmantoro; Juliana M. Sumilat (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
This research aims to develop MONOTIKA learning media (Monopoly Mathematics) and test the feasibility of MONOTIKA learning media (Monopoly Mathematics) in algebraic materials for middle school students. The learning development model is the ADDIE design model. This study's sources of needs analysis are SMP Negeri 126 and SMP Negeri 209 east Jakarta area. Data collection techniques used are teacher interviews and polling stations. Validation of the development of this learning media between 2 validators is material experts and media experts and students response usage if MONOTIKA media is used in schools. This media trial was conducted on 41 students in grades 7 G and 7 H at SMP Negeri 209 Jakarta. This study showed that MONOTIKA (Monopoly Mathematics) obtained a total average score for all aspects of all is 4.50 material expert validity and 4.28 valid expert media, which is an average media that deserves good both as a learning medium. Student poll results showed an average score of 4.47, which the average student gave responsibility for positive MONOTIKA (Monopoly Mathematics). Thus, the results of the development of MONOTIKA (Monopoly Mathematics) learning media for junior high school students in grade VII are valid and eligible for use.